Analisis Risiko Pengolahan Limbah Bahan Berbahaya dan Beracun dengan Cara Termal Melalui Insinerasi (Studi Kasus: PT. XYZ) - Surya Adi Wicaksono; Joyosemito , Ibnu Susanto; Haudi Hasaya (Jurnal Serambi Engineering, 2025)
Rapid industrial growth increases the production of hazardous and toxic waste (LB3), which, if not managed properly, can pose a serious risk to human health and the environment. This study analyses the risks associated with the incineration of hazardous waste at PT XYZ, using the Hazard Identification, Risk Assessment and Risk Control (HIRARC) approach based on the AS/NZS 4360:2004 standard. Hazard identification is conducted via Job Safety Analysis (JSA), while risk assessment considers likelihood and severity. The results show that the infectious waste feeding process and combustion emissions pose the greatest risk (high and very high), with potential consequences including exposure to chronic diseases and environmental pollution. Risk control is achieved by providing personal protective equipment (PPE), monitoring flue gas emissions and managing incinerator residues in accordance with regulations. This study highlights the importance of implementing strict risk management measures and technological innovations to mitigate the negative impacts of hazardous waste incineration.